Literary Ecocriticism Study in Analyzing Elements of Environmental and Social Resistance in Wiji Thukul’s Poems - Christina Astrilinda Purnomo (Hasanuddin University, 2024)
This study employs literary ecocriticism theory to examine elements of environmental and social resistance in Wiji Thukul’s poetry. Wiji Thukul is a poet from the '98 generation, known for his provocative and vibrant works. The connection between literary works and elements of environmental and social resistance is prevalent in Wiji Thukul's poetry. Literary ecocriticism is applied to analyze his poetry using a qualitative descriptive method. The ecocritical analysis of Wiji Thukul’s poetry offers insights into the ecological issues related to environmental and social resistance reflected in his poems. Seven of his poems will be analyzed in this study: Leuwigajah, Bunga dan Tembok, Nyanyian Akar Rumput, Sajak Anak-Anak, Nyanyian Tanah Ibu, Di Bawah Selimut Kedamaian Palsu, and Sajak Tikar Plastik - Tikar Pandan. The results indicate that Wiji Thukul’s poems, when analyzed through literary ecocriticism, reveal elements of environmental and social resistance that serve as a critique of the government and as a means of raising public awareness about the deteriorating environmental conditions.